PRESENCE OF CITRININ IN GRAINS AND ITS POSSIBLE HEALTH EFFECTS - Čulig, CleBorna; Bevardi, Martina; Bošnir, Jasna; Serdar, Sonja; Lasić, Dario; Lasić, Dario; Racz, Aleksandar; Galić, Antonija; Kuharić, Željka (African Journal of Traditional, Complementary and Alternative Medicines, 2017)
Background: Citrinin is a mycotoxin produced by several species of the genera Aspergillus, Penicillium and Monascusand it occurs mainly in stored grain. Citrinin is generally formed after harvest and occurs mainly in stored grains, it alsooccurs in other plant products. Often, the co-occurrence with other mycotoxins is observed, especially ochratoxin A,which is usually associated with endemic nephropathy. At the European Union level, systematic monitoring of Citrininin grains began with the aim of determining its highest permissible amount in food. Thus, far the systematic monitoringof the above mentioned mycotoxin in Croatia is yet to begin.Materials and Methods: The main goal of this study was to determine the presence of Citrinin in grains sampled in thearea of Međimurje, Osijek-Baranja, Vukovar-Srijem and Brod-Posavina County. For the purpose of identification andquantification of citrinin, high performance liquid chromatograph (HPLC) with fluorescence was used (Calibrationcurve k ≥ 0.999; Intra assay CV = 2.1%; Inter assay CV = 4.3%; LOQ < 1 μg/kg).Results: From the area of Međimurje County, 10 samples of corn and 10 samples of wheat were analyzed. None of thesamples contained Citrinin (<1 μg/kg). From the area of Osijek-Baranja and Vukovar-Srijem County, 15 samples fromeach County were analyzed. The mean value for the samples of Osijek-Baranja County was 19.63 μg/kg (median=15.8μg/kg), while for Vukovar-Srijem County the mean value of citrinin was 14,6 μg/kg (median=1.23 μg/kg). From 5analyzed samples from Brod-Posavina County, one of the samples contained citrinin in the amount of 23.8 μg/kg, whilethe registered amounts in the other samples were <1 μg/kg.Conclusion: The results show that grains from several Counties contain certain amounts of Citrinin possibly indicatinga significant intake of citrinin in humans. It must be stated that grains and grain-based products are the basis ofeveryday diet of all age groups, especially small children, where higher intake of citrinin can occur. Consequently, weemphasize the need for systematic analysis of larger amount of samples, from both large grains and small grains,especially in the area of Brod-Posavina County, in order to obtain more realistic notion of citrinin contamination ofgrains and to asses the health risk in humans.